Examining relationship between unhealthy lifestyle and life satisfaction among new students at Tehran University of Medical Sciences - Mohamad Eshaghi; Keyvan Karimi; Nekoo Panahi; Yosra Azizpour; Farideh Razi; Anis Gharajeh; Samaneh Akbarpour; Fatemeh Hadavandsiri (PLoS ONE, 2026)
Background Transitioning to university is a critical period marked by lifestyle changes, academic pressures, and increasing autonomy, which can influence students’ overall well-being. Previous research suggests that unhealthy lifestyle behaviors—including poor diet, insufficient physical activity, inadequate sleep, and ineffective stress management—may negatively impact life satisfaction among young adults. Methods This cross-sectional study examined the relationship between lifestyle and life satisfaction among newly enrolled undergraduate students at Tehran University of Medical Sciences in 2024. Participants completed structured questionnaires assessing multiple lifestyle domains (diet, physical activity, sleep, smoking, alcohol use) and life satisfaction using validated Iranian questionnaires. Lifestyle scores were categorized as “healthy” or “unhealthy,” and life satisfaction as “good” or “poor.” Associations were analyzed using Pearson’s chi-square test and multivariable logistic regression, adjusting for age, sex, socioeconomic status, and anxiety. Results Overall, of the 419 students, 294 (70.2%) reported good life satisfaction. Socioeconomic status and anxiety levels differed significantly across life satisfaction groups (p < 0.001). Students with healthier dietary patterns reported higher life satisfaction (76.6% vs. 60.4%, p = 0.02). Multivariable analysis indicated that students with healthy lifestyles had significantly higher odds of good life satisfaction compared to those with unhealthy lifestyles (adjusted odds ratio [aOR = 1.91; 95% confidence interval [CI]: 1.10,3.35; p = 0.02). Each one-unit increase in lifestyle score was associated with a 28% increase in the odds of good life satisfaction (aOR = 1.28; 95% CI: 1.05,1.57; p = 0.02). Conclusion Unhealthy lifestyle behaviors are negatively associated with life satisfaction among new university students. Interventions promoting balanced nutrition, regular physical activity, adequate sleep, and overall health-conscious behaviors may enhance students’ life satisfaction and well-being.